1995
DOI: 10.1111/j.1460-9568.1995.tb01047.x
|View full text |Cite
|
Sign up to set email alerts
|

Eye Position Influence on the Parieto‐occipital Area PO (V6) of the Macaque Monkey

Abstract: The aim of this work was to study the effect of eye position on the activity of neurons of area PO (V6), a cortical region located in the most posterior part of the superior parietal lobule. Experiments were carried out on three awake macaque monkeys. Animals sat in a primate chair in front of a large screen, and fixated a small spot of light projected in different screen locations while the activity of single neurons was extracellularly recorded. Both visual and non-visual neurons were found. About 48% of vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
258
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 262 publications
(285 citation statements)
references
References 41 publications
25
258
0
Order By: Relevance
“…Gain modulation of spatially selective neurons is the key principle underlying the spatial transformation mechanism in this model, similar to previous models of multisensory integration for spatial reference frame transformations (Zipser and Andersen, 1988;Salinas and Abbott, 1996). Gain modulation during multisensory integration for eye or hand movements had previously been found in the posterior parietal cortex (Andersen et al, 1985;Brotchie et al, 1995;Galletti et al, 1995;Snyder et al, 1998;Batista et al, 1999;Nakamura et al, 1999;Buneo et al, 2002) and frontal areas (Boussaoud et al, , 1998Mushiake et al, 1997;Cisek and Kalaska, 2002). In contrast, here we have shown gain modulation effects in PRR and PMd for remapping visuospatial information onto reach motor goals according to abstract cognitive transformation rules.…”
Section: Contextual Modulations In Prr and Pmdmentioning
confidence: 44%
See 2 more Smart Citations
“…Gain modulation of spatially selective neurons is the key principle underlying the spatial transformation mechanism in this model, similar to previous models of multisensory integration for spatial reference frame transformations (Zipser and Andersen, 1988;Salinas and Abbott, 1996). Gain modulation during multisensory integration for eye or hand movements had previously been found in the posterior parietal cortex (Andersen et al, 1985;Brotchie et al, 1995;Galletti et al, 1995;Snyder et al, 1998;Batista et al, 1999;Nakamura et al, 1999;Buneo et al, 2002) and frontal areas (Boussaoud et al, , 1998Mushiake et al, 1997;Cisek and Kalaska, 2002). In contrast, here we have shown gain modulation effects in PRR and PMd for remapping visuospatial information onto reach motor goals according to abstract cognitive transformation rules.…”
Section: Contextual Modulations In Prr and Pmdmentioning
confidence: 44%
“…Based on our data, we propose that gain modulation is used by the brain not only in sensorimotor areas to achieve reference frame transformations driven by multisensory input (Andersen et al, 1985;Zipser and Andersen, 1988;Boussaoud et al, , 1998Brotchie et al, 1995;Galletti et al, 1995;Buneo et al, 2002), but also in the frontoparietal reach network to achieve contextually modulated, goal-directed visuomotor remapping, as previously suggested theoretically (Salinas, 2004;Brozovic´et al, 2007). Our current data support this idea by providing first experimental evidence for context-specific gain modulations of spatial motor-goal tuning in PRR and PMd, which could denote the key underlying principle of flexible goal-directed behavior.…”
Section: Gain Modulation As Universal Mechanism For Flexible Remappingmentioning
confidence: 92%
See 1 more Smart Citation
“…14 and 25) should have pushed the functional area V6 from the medial fundus of the parieto-occipital sulcus in monkeys (22) to the upper posterior wall of the parietooccipital sulcus and thus to the anteromedial cuneus in humans. The neurons of V6 have large receptive fields (22), and lack enhanced foveal magnification both in monkeys (22) and humans (26), and the area has been suggested to participate in visuospatial analysis of environment for arm reaching and eye movements (27,28). The human anteromedial cuneus could also contain an area or multiple areas with no equivalent in the macaque brain.…”
Section: Resultsmentioning
confidence: 99%
“…Several neurophysiological studies have shown that the activity of neurons in many PPC areas is modulated by gaze direction (Sakata et al, 1980;Mountcastle, 1981;Andersen and Mountcastle, 1983;Andersen et al, 1990;Galletti et al, 1995;Squatrito and Maioli, 1996;Bremmer et al, 1997Bremmer et al, , 2001Nakamura et al, 1999), but few have demonstrated that single PPC neurons are modulated by vergence (Sakata et al, 1980;Genovesio and Ferraina, 2004;Genovesio et al, 2007;Bhattacharyya et al, 2009). The encoding of both direction of gaze and depth of fixation in single PPC neurons has been to date reported only in area 7a (Sakata et al, 1980).…”
Section: Introductionmentioning
confidence: 99%